(untitled) (Philological Studies, 2019)
This paper presents the results of contemporary field research regarding the traditional forms of mediating well-wishing and gift-bearing in the context of New Year celebrations. We single out the verbal codes from the complex of rituals and customs that include masquerading, processions, hospitality and blessings, and view them as symbolic structures containing complex meanings, analogous to the formulae of oral poetry, and helpful for a reconstruction of the world image inherent the Serbian traditional culture. We also discuss the possibility to define the ritual-customary masquerading as a carnival and to define that widespread local practice as intagible cultural heritage.